Including students with autism in schools: a whole school approach to improve outcomes for students with autism. Issue 7 (7th June 2022) - Roberts, Jacqueline; Webster, Amanda
ABSTRACT: In the last two decades there has been a rapid increase in the number of students with autism who are enrolled in mainstream schools. Since the publication of the Salamanca Statement in 1994, the right to inclusive education for all children, including those with disabilities, has been increasingly recognised. This has created tensions and challenges in schools as staff struggle to meet the unique needs of these students and their families. Previous research has found that school staff often lack knowledge about the specific characteristics and needs of students with autism and the practices that effectively support these students in inclusive education settings. A comprehensive approach is needed to build capacity of school leaders and staff to create autism-friendly cultures, implement evidence-based strategies, and improve outcomes for students with autism. This paper describes the development and theoretical foundation of the School-wide Autism Competency approach, which provides schools with a whole-of-school approach to supporting students with autism. The approach brings together research on effective practices of school leaders and evidence-based practices for students with autism.